Experimental Study on Wake Development in a Three-cylinder Model within a Tunnel in Transitional Flow. Issue 17 (8th November 2018) - Zhou, Shaodong; Zhou, Jie; Zhao, Liang; Xi, Guannan
ABSTRACT: The characteristics of the flow and heat transfer in transitional flow are not clear and especially the lack of some reliable experimental data hinders the numerical study of the heat exchanger. Based on this, a two-dimensional time-resolved digital particle image velocimetry from the American-TSI-corporation was adopted. Experiments were carried out in an open-loop, recirculating water tunnel that operated at steady-state conditions. The experimental object is a three-cylinder with an equilateral triangle configuration having center-to-center distance ratio of 3. Reynolds number based on the tube diameter and the velocity of inlet is set at 70, 90, 120, 150, 200, 250 and 300. The flow parameters were quantified to research the effect of Reynolds number on flow field for supporting some facts to analyze the heat transfer. Time-mean flow field, turbulence statistics and velocity processed by proper orthogonal decomposition were investigated at different Reynolds numbers. The wake closure length, oscillation and Karman vortex in the wake of the three-cylinder model were discussed in detail.